AI Used in Electronic Traffic Law Enforcement as Law Enforcement Evidence in Digital Era - Hasibuan, Edi Saputra (International Journal Labs, 2023)
Background: It is undeniable that in the revolutionary era, technological advances developed so rapidly and had an impact on the legal system in Indonesia. To keep up with these developments, the use of artificial intelligence as a national legal instrument is very important. Aim: This research was done to find out how important the sustainable development of law is and to explore the potential of using artificial intelligence in improving efficiency, justice and law enforcement in the digital era through Electronic Traffic Law Enforcement (ETLE). Method: In this study, the authors used a normative type of juridical research. This research is intended to determine the need for legal development in digital and the role of ETLE as evidence of law enforcement in the digital era. Findings: Indonesia's positive law must adapt to technological advancements to ensure justice, certainty, and community benefits. Utilizing national legal support facilities and infrastructure, particularly law enforcement, is crucial in the digital era.